2011
DOI: 10.1007/s10551-011-0820-2
|View full text |Cite
|
Sign up to set email alerts
|

Moral Differentiation: Exploring Boundaries of the “Monkey See, Monkey Do” Perspective

Abstract: ethical decision making, extraversion, interpersonal distancing, moral differentiation, moral identity, need for affiliation,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 118 publications
(167 reference statements)
1
35
0
1
Order By: Relevance
“…However, even when the well-validated measure developed by Aquino and Reed [2002] was used, no age differences between 15-and 20-year-olds were found [Krettenauer & Casey, in press]. Similar findings were reported in studies with young adults [Gu, 2011;Matherne & Litchfield, 2012;McFerran, Aquino, & Duffy, 2010;O'Fallon & Butterfield, 2011;Reynolds, Dang, Yam, & Leavitt, 2014]. All these studies replicated the finding from the very first study on adolescent moral identity development conducted by Arnold [1993] that did not reveal any relationship between the self-rated importance of moral virtues and adolescents' age.…”
Section: The Empirical Challenge: Lack Of Evidence For Developmental supporting
confidence: 58%
“…However, even when the well-validated measure developed by Aquino and Reed [2002] was used, no age differences between 15-and 20-year-olds were found [Krettenauer & Casey, in press]. Similar findings were reported in studies with young adults [Gu, 2011;Matherne & Litchfield, 2012;McFerran, Aquino, & Duffy, 2010;O'Fallon & Butterfield, 2011;Reynolds, Dang, Yam, & Leavitt, 2014]. All these studies replicated the finding from the very first study on adolescent moral identity development conducted by Arnold [1993] that did not reveal any relationship between the self-rated importance of moral virtues and adolescents' age.…”
Section: The Empirical Challenge: Lack Of Evidence For Developmental supporting
confidence: 58%
“…Likewise, Ferguson & Barry (2011) report that group cohesion increases the relationship between an employee being a direct observer of interpersonal deviance by coworkers and the employee also engaging in interpersonal deviance. Consistent with this perspective, O'Fallon & Butterfield (2011) found that employees with a low need for affiliation are less likely to copy their coworkers' unethical behaviors. These authors also developed and tested an important construct-moral differentiation-that may explain why and when certain individuals are resistant to copying the dysfunctional behavior of their coworkers.…”
Section: Social Distancementioning
confidence: 78%
“…In general, research has shown that contexts that reinforce ethical behavior (e.g., ethical culture, Caldwell & Moberg, ; charitable giving by an organization; Reed, Aquino, & Levy, ; recognition of donation behavior, Winterich, Mittal, & Aquino, 2013; priming moral context, Aquino et al, ; recognition of a focal actor's prosocial behavior, Winterich, Aquino, Mittal, & Swartz, 2013) generally influence ethical behavior, particularly for individuals with greater moral centrality. Contexts that impair self‐regulatory functioning or heighten self‐interest fuel unethical behavior (observed coworker unethical behavior, O'Fallon & Butterfield, ; power, DeCelles, DeRue, Margolis, & Ceranic, ; primed self‐interest, Skarlicki & Rupp, ; mistreatment, Skarlicki, van Jaarsveld, & Walker, ), particularly for those with lower moral centrality. Additionally, Hannah and Avolio () found that dimensions of moral strength can reinforce one another: The positive effects of moral ownership on ethical behavior were further enhanced for individuals with stronger moral courage; individuals high in both moral courage and moral ownership were more likely to confront others for their unethical acts.…”
Section: Review Of Empirical Research On the Moral Selfmentioning
confidence: 99%